Chaos kings : how Wall Street traders make billions in the new age of crisis - Patterson, Scott, 1969- (Scribner, 2023)
"There's no doubt that our world has gotten more extreme. Pandemics, climate change, superpower rivalries, cyberattacks, political radicalization--virtually, everywhere we look there is mayhem bearing down on us, putting trillions of assets at risk. And at least two factions have formed around how to respond. In Chaos Kings, Scott Patterson depicts how one faction, led by Nassim Nicholas Taleb, bestselling author of The Black Swan, believes humans can never see the big disaster coming. In their view, extreme events--so-called Black Swans--while inevitable, will always catch us by surprise. In 2007, Taleb's longtime collaborator, Mark Spitznagel, launched the Universa hedge fund, which would go on to make billions protecting investors against unforeseen chaos in the market. A second faction, which relies on complex formulas, believes looming chaos can be detected. Chief among these risk prognosticators is Didier Sornette, a colorful French mathematician who enjoys riding his motorcycle at speeds in excess of 170 miles per hour. When Sornette looks out from what he calls his Financial Crisis Observatory in Zurich, Switzerland, what he sees are Dragon Kings--punishing events that are unlikely to occur but have probabilities that can be predicted... and defended against. Which faction is right? All of our financial futures may depend on the answer"--